2009
DOI: 10.1253/circj.cj-08-0339
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Non-Compaction of the Ventricular Myocardium Associated With Long QT Syndrome A Report of 2 Cases

Abstract: solated non-compaction of the ventricular myocardium (INCVM) is a relatively newly defined disorder of the endomyocardium characterized by prominent ventricular trabeculations and deep intertrabecular recesses. 1 Clinical manifestations include a depressed left ventricular (LV) function, ventricular arrhythmia, and systemic embolization. 2,3 INCVM has been reported to be associated with several electrocardiographic changes such as ST depression and flat or negative T waves, bundle branch block, and Wolff-Parki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
1
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 12 publications
2
16
1
2
Order By: Relevance
“…Indeed, both benign as well as life-threatening arrhythmias, including VT and ventricular fibrillation, may readily be encountered in these patients. 4,9,25, 26 In the current study, none of the ECG parameters was predictive of severe ventricular arrhythmias during follow-up. Identifying patients likely to suffer malignant ventricular arrhythmias hence remains a challenge in patients with IVNC.…”
Section: Discussioncontrasting
confidence: 45%
“…Indeed, both benign as well as life-threatening arrhythmias, including VT and ventricular fibrillation, may readily be encountered in these patients. 4,9,25, 26 In the current study, none of the ECG parameters was predictive of severe ventricular arrhythmias during follow-up. Identifying patients likely to suffer malignant ventricular arrhythmias hence remains a challenge in patients with IVNC.…”
Section: Discussioncontrasting
confidence: 45%
“…From that time, they mature by cardiomyocyte recruitment and proliferation [3,46]. Between gestational weeks 5 and 8, the developing myocardium gradually condenses and the intertrabecular spaces flatten and disappear coinciding with the developing coronary vasculature [3,46,55]. This process typically progresses from the epicardium to the endocardium, from the base to the apex, and is more pronounced in the left than the right ventricle [56].…”
Section: Congenital Lvhtmentioning
confidence: 99%
“…Single LVHT patients may present with hereditary sick-sinus syndrome or long-QT syndrome due to mutations in the cardiac sodium-or potassium channels ( Table 1). The 24-h Holter monitoring may reveal sinusbradycardia, ventricular bigeminia, nonsustained ventricular tachycardia [76], T-wave alternans, or torsades de pointes [55], but some authors regard Holter monitoring as insufficient to detect ventricular tachycardias and propose loop recording [76]. Whether ECG abnormalities other than severe ventricular arrhythmias have prognostic implications is unknown, but in a study on 78 LVHT patients, a striking overlap between ventricular conduction delay, atrial conduction delay, QT-prolongation, atrial dilatation, and systolic dysfunction was found [72].…”
Section: Electrocardiographic Abnormalitiesmentioning
confidence: 99%
“…8 LVNC has also been observed in conjunction with inherited long QT syndrome secondary to KCNH2 mutations; Ogawa et al described one pediatric patient with an A561V mutation in the pore region, and another with a D501N mutation in the nonpore region. 9 Furthermore, it has been associated with the ryanodine receptor gene (RYR2) exon 3 deletion that is described to be a causative mutation in catecholaminergic ventricular tachycardia (CPVT) and in dilated cardiomyopathy. In a series published by Ohno et al, two unrelated individual CPVT probands, each with large RYR2 exon 3 deletions, and concomitant LVNC, were identified.…”
Section: Genetic Basismentioning
confidence: 99%
“…The authors raise the concern regarding the higher risk of SCD in such patients, and recommend the implantation of an ICD. 31 Campbell et al described an interesting case of CPVT occurring in a patient who developed LVNC, and who was found to have deletion of exon 3 of the RYR2 gene encoding the ryanodine receptor. This patient suffered multiple expertional syncopal episodes as a child and adolescent, with one episode occurring with documented AF.…”
mentioning
confidence: 99%